Pengaruh Kompensasi Terhadap Kinerja Karyawan Pada RSU Natama - Batubara, Rizki Wulanita; Roni, Shofyan (Sekolah Tinggi Ilmu Ekonomi Bina karya, 2025)
This study aims to examine the influence of compensation on employee performance at RSU Natama. Where data will be collected through distributing questionnaires to 32 respondents who are employees of RSU Natama, using the census method. The data obtained were then analyzed using a quantitative approach, which includes validity and reliability tests, classical assumption tests, hypothesis tests through t-tests, and analysis of the coefficient of determination (R²) using the SPSS 25 statistical analysis tool.